EVALUATION OF THE DIGITAL TRANSFORMATION POLICY OF ELECTRONIC MEDICAL RECORDS (EMR) ON THE QUALITY OF HEALTHCARE SERVICES AT DR. RUBINI MEMPAWAH REGIONAL GENERAL HOSPITAL - Nengsih Juniarti; Yulius Yohanes; Isdairi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This research is entitled: Evaluation of the digital transformation policy process of Electronic Medical Records (ERM) on the quality of health services at Dr. Ribini Mempawah Regional General Hospital. The problems of this research stem from the lack of Human Resources Competence in ERM Operation, not yet Optimal Security and Privacy of Patient Data, not yet Optimal Data Integration between Service Units, Limited Maintenance and Limited Technical Support and limited Infrastructure and Internet Network. The purpose of this research is to describe and analyze the compliance perspective and what's happening perspective in the Evaluation of the digital transformation policy process of Electronic Medical Records (ERM) on the quality of health services at Dr. Ribini Mempawah Regional General Hospital. This research uses a descriptive research type with a qualitative approach. The results of the study indicate that the implementation of the ERM policy at Dr. Ribini Mempawah Regional General Hospital has been carried out but is not optimal. From a compliance perspective, the compliance of implementing agents is quite good although not yet consistent, the implementation of the policy has not been fully integrated between units, and facilities and resources still need strengthening. From a what's happening perspective, implementation is influenced by HR readiness, management support, technological infrastructure, and work culture, while short-term results show an increase in administrative efficiency and ease of access to patient data. This study recommends strengthening human resource capacity, improving infrastructure, and optimizing coordination and oversight to support the success of digital transformation and improve the quality of healthcare services.